BRAND IMAGE PEMEDIASI PENGARUH ADVERTISING DAN BRAND AMBASSADOR IDOL K-POP PADA KEPUTUSAN PEMBELIAN DI TOKOPEDIA - Livia Widya Purnama; Dwi Novitasari (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
This study aims to determine the effect of advertising and brand ambassadors on purchasing decisions mediated by brand image at the Tokopedia Company. The population in this study is the people of Yogyakarta who have made online purchases at Tokopedia. The sample used in this research is 100 people with the criteria (1) respondents have used and have a Tokopedia account and are domiciled in Yogyakarta. (2) have made online purchases at Tokopedia at least 3 times. (3) able to mention at least 3 advantages of the Tokopedia application. (4) knowing the Tokopedia brand ambassador for the past year. The instrument of this research is a questionnaire on google form with validity test using convergent validity and discriminant validity, and reliability test using AVE, Cronbach alpha and composite reliability. Data analysis using Structural Equation Model (SEM). The results of this study indicate that advertising has a positive effect on brand image at Tokopedia. Brand ambassadors have a positive effect on the brand image of Tokopedia. Brand image has a positive effect on purchasing decisions at Tokopedia. Advertising has a positive effect on purchasing decisions at Tokopedia. Brand ambassadors have a negative effect on purchasing decisions at Tokopedia. Advertising has a negative effect on purchasing decisions mediated by brand image on Tokopedia. Brand ambassadors influence purchasing decisions mediated by brand image on Tokopedia.